2017
DOI: 10.1186/s12935-017-0411-0
|View full text |Cite
|
Sign up to set email alerts
|

High expression of Rab25 contributes to malignant phenotypes and biochemical recurrence in patients with prostate cancer after radical prostatectomy

Abstract: BackgroundRas-related protein 25 (Rab25) functions either as an oncogene or a tumor suppressor with a cancer type-dependent manner. We aimed to investigate clinical significance of Rab25 in prostate cancer (PCa).MethodsQuantitative real-time polymerase chain reaction, Western blot and immunohistochemistry were respectively performed to detect Rab25 mRNA and protein expression in PCa and adjacent non-cancerous prostate tissues. Receiver-operating characteristic curve analysis was used to evaluate predictive dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Members of the RAB family regulate vesicle trafficking and are known to both promote and suppress tumor growth, depending on the family member and cancer type [34]. Although increased expression of RAB25 has been shown to contribute to prostate cancer malignancy and recurrence [35], similar studies or observations involving RAB17 are lacking.…”
Section: Cancer-specific Featuresmentioning
confidence: 99%
“…Members of the RAB family regulate vesicle trafficking and are known to both promote and suppress tumor growth, depending on the family member and cancer type [34]. Although increased expression of RAB25 has been shown to contribute to prostate cancer malignancy and recurrence [35], similar studies or observations involving RAB17 are lacking.…”
Section: Cancer-specific Featuresmentioning
confidence: 99%
“…Rab25 functions either as an oncogene or a tumor suppressor with a cancer type-dependent manner. It was predominantly reported to have oncogenic function and elevated expression in cancer, including ovarian cancer [ 12 , 13 ], breast cancer [ 12 14 ], renal cancer [ 15 , 16 ], gastric cancer [ 17 ], liver cancer [ 18 ], non-small cell lung cancer [ 19 ], bladder cancer [ 20 ], glioblastoma multiforme [ 21 ] and prostate cancer [ 22 ]. Tumor suppressor function of Rab25 has also been found in several types of cancer, including colon cancer [ 23 ], head and neck cancer [ 24 ], esophageal squamous cell carcinoma [ 25 ] and oral and oropharyngeal squamous cell carcinoma [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that Rab25 enhances cell proliferation and tumor development. Knockdown of Rab25 expression by siRNA / shRNA transfection inhibited in vitro cell growth of renal cell carcinoma cells (786-O and A-498) [ 16 ], prostate cancer cells (LNCaP) [ 22 ] and hepatocellular carcinoma cells (Bel7402 and SK-Hep-1) [ 45 ]. Suppression of both in vitro cell growth and in vivo xenograft development were observed after knockdown of Rab25 in glioblastoma multiforme cells (U87MG) [ 21 ] and breast cancer cells (MCF7) [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations